The Influence of Medication Non-Adherence on the Occurrence of Drug-Resistant Tuberculosis - Handayani, Reni Stefhanie; Hendarwan, Harimat; Ratri, Teja (Journal of Current Health Sciences, 2024)
Drug-resistant tuberculosis (DR-TB) presents a significant challenge to global TB control efforts, with medication non-adherence identified as a major contributing factor. This study aimed to investigate the influence of medication non-adherence on the occurrence of DR-TB in Serang City, Indonesia. Utilizing an observational analytic study with a case-control design, the research included 76 TB patients, comprising 38 DR-TB cases and 38 drug-sensitive TB controls. Data were collected from secondary sources and validated questionnaires and analyzed using univariate and bivariate methods, including Chi-square tests and Odds Ratios (OR). The findings revealed a significant relationship between medication non-adherence and DR-TB, with an OR of 11.56, indicating that non-adherent patients are 11.5 times more likely to develop DR-TB compared to adherent patients. However, demographic factors such as age, occupation, and education did not significantly influence the incidence of DR-TB. The study concludes that medication non-adherence is a critical risk factor for the development of DR-TB, underscoring the need for targeted interventions to improve treatment adherence, particularly through educational campaigns and community-based support. Health authorities are encouraged to implement intensive educational programs focused on the risks of non-adherence and ensure that TB treatment is accessible and supported by community health workers. Policymakers should allocate sufficient resources to these initiatives to effectively reduce the incidence of DR-TB.